1996
DOI: 10.1111/j.1365-2621.1996.tb14175.x
|View full text |Cite
|
Sign up to set email alerts
|

Foaming and Emulsifying Properties of Whey Protein Concentrates As Affected by Lipid Composition

Abstract: Freeze-dried WPC, containing 35 and 75% protein were manufactured by pretreating whey with calcium chloride and heat. These and commercial WPC were subjected to proximate analysis and lipid classes, phospholipid classes, free fatty acids (FFA), and monoacylglycerols (MAG) composition were determined. Solubility, thermal, foaming, and emulsifying properties of the WPC were studied. Pretreatment increased calcium and phosphorus contents and decreased the contents of all other minerals. The pretreatment had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…The drying method did not have statistically significant effects on the solubility of native WPC powders. A similar result was observed also by Vaghela and Kilara (1996). Bhargava and Jelen (1995) found that freezing of liquid WPC had no effect on its functional properties.…”
Section: Resultssupporting
confidence: 90%
“…The drying method did not have statistically significant effects on the solubility of native WPC powders. A similar result was observed also by Vaghela and Kilara (1996). Bhargava and Jelen (1995) found that freezing of liquid WPC had no effect on its functional properties.…”
Section: Resultssupporting
confidence: 90%
“…This may be due to the presence of residual fat, which decreased the emulsification properties. Similar findings were reported by Vaghela and Kilara () and Sanmartín et al . ().…”
Section: Resultssupporting
confidence: 92%
“…The protein contents varied from 22.0% to 30.5%, these being lower than the typical protein composition for a 35% WPC, which usually varies from 34% to 37% (Vaghela & Kilara, 1996). Consequently, the fat and lactose contents were higher than the typical WPC, the fat content being between 6.9% and 13.4% and the lactose content between 49.7% and 62.2%.…”
Section: Resultsmentioning
confidence: 93%